(untitled) (Agora for Physical Education and Sport, 2020)
The purpose of this paper is to continue the inquiry about Soviet sport. Leaning on the relevant historiographical bibliography, I will address the problem of amateurism and professionalism in the period that covered the Second World War until the fall of the USSR, referring to the sports model of that State. In this way, I intend to complete what I started in a previous work, which covered the first years of Soviet sport, in order to provide a perspective that allows us to observe the development of those aspects of sport that were potentially developed in those times.